Enhanced Electrical and Mechanical Properties of a Printed Bimodal Silver Nanoparticle Ink for Flexible Electronics. Issue 14 (12th June 2018) - Liu, Zhongyang; Ji, Hongjun; Wang, Shuai; Zhao, Weiwei; Huang, Yan; Feng, Huanhuan; Wei, Jun; Li, Mingyu
Abstract : Electrical patterns that can be formed with high electrical conductivity and mechanical robustness under mild conditions are critical for developing flexible electronics with heat‐sensitive substrates. Here, the authors synthesize bimodal Ag nanoparticle (AgNP) inks by mixing two sizes of AgNPs (10 and 50 nm) and sintering them at room temperature in air on photopaper without any heat or chemical treatment. The optimized particle size ratio, sintered microstructures, and properties of the bimodal inks are systematically investigated and compared with those of the unimodal inks. These inks are printed and sintered at room temperature in air using accurate and controllable washing processes. An optimized resistivity as low as 3.66×10 −6  Ω cm is obtained when the ratio of the 10 nm AgNPs to the 50 nm AgNPs is 2:1. The bimodal ink could be printed in a short time and exhibited good bending performance with reduced coffee‐ring defects. The enhanced performance indicates that even just by matching the particle sizes and using the appropriate cleaning process, the bimodal AgNPs ink could be sintered with uniform morphologies throughout the repeated printing process to achieve a remarkably low resistivity. The proposed water‐based bimodal AgNP ink will enable one‐step inkjet printing and sintering for the first time with improved properties and convenience for developing highly sensitive flexible substrates and devices. Abstract : Bimodal two‐sized AgNPs ink through multi‐cleaning is printed and sintered at room temperature with highly improved electrical and mechanical properties.